Multi-scale data on intertidal macrobenthic biodiversity and environmental features in Kaipara, Tauranga, and Manukau Harbours, New Zealand - Casper Kraan; Barry L Greenfield; Simon F Thrush (PANGAEA, 2019)
Within the project Spatial Organization of Species Distributions: Hierarchical and Scale-Dependent Patterns and Processes in Coastal Seascapes at the National Institute for Water and Atmospheric Research (NIWA) in New Zealand we collected multi-scale (30cm to 1km) and high resolution data (3 x 400 cores) on macrobenthic biodiversity (146 species), i.e. bivalves, polychaetes and crustaceans (> 500μm) that live hidden in marine sandflats, and point measurements of important environmental variables (3 x 320 samples), i.e. sediment grain-size distributions measured with a Malvern Mastersizer, chlorophyll a concentrations measured by a fluorometer, and visible sandflat parameters whose coverage was estimated from photos, in three large intertidal Harbours (Kaipara, Tauranga and Manukau). In each Harbour we sampled 400 points for macrobenthic community composition and abundances, as well as the full set of environmental variables, covering spatial scales of a few centimetres to a maximal extent of 1 km. The six tables can be joined by the field "label[ID]", whereas the field [species_abbreviation] can be linked to the species-list (Table 1) to obtain the full scientific name.